1966
DOI: 10.1901/jeab.1966.9-641
|View full text |Cite
|
Sign up to set email alerts
|

FREE OPERANT AVOIDANCE AS A FUNCTION OF THE RESPONSE‐SHOCK = SHOCK‐SHOCK INTERVAL1

Abstract: Two temporal parameters of free operant or Sidman avoidance behavior are the interval by which responses postpone shocks (Response-Shock interval) and the interval between shocks when no responses occur (Shock-Shock interval). Avoidance behavior was examined in three white rats under conditions where the Response-Shock and Shock-Shock intervals were always equal. With intervals from 10 to 60 sec response rates and shock rates were similar, decreasing, negatively accelerated functions of increasing Response-Sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
21
2

Year Published

1967
1967
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 9 publications
9
21
2
Order By: Relevance
“…The differences can be readily attributed to the preselection of proficient avoiders in most studies; rats that in preliminary training have produced especially low shock rates would be expected to persist more than do the less-proficient animals on procedures with marginal reinforcing consequences for responding. Clark and Hull (1966) reported no irreversible effects resulting from exposure to short SS = RS intervals. In the present work, such irreversible effects were observed when such exposures occurred relatively early in training, as indicated by the necessity for deleting two animals given early exposure to short intervals, and by the inferior performance levels shown by the third such animal (Figure 1).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The differences can be readily attributed to the preselection of proficient avoiders in most studies; rats that in preliminary training have produced especially low shock rates would be expected to persist more than do the less-proficient animals on procedures with marginal reinforcing consequences for responding. Clark and Hull (1966) reported no irreversible effects resulting from exposure to short SS = RS intervals. In the present work, such irreversible effects were observed when such exposures occurred relatively early in training, as indicated by the necessity for deleting two animals given early exposure to short intervals, and by the inferior performance levels shown by the third such animal (Figure 1).…”
Section: Discussionmentioning
confidence: 94%
“…Using two rats, Herrnstein and Brady (1958) examined a set of smaller intervals, ranging from 5 to 20 sec, embedded in a multiple schedule that included appetitive behavior. Using three rats, Clark and Hull (1966) examined intervals ranging from 10 to 60 sec. All four experiments produced functions of approximately the same shape, resembling hyperbolic, or logarithmic relations between response rate and the SS = RS interval; their data gave approximately linear functions when rate was plotted against the reciprocal of the interval, at least over the ranges of intervals that were used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present study sought to discover if lever holding was correlated with the principal parameter of the freeoperant avoidance schedule, the responseshock interval. Studies by Sidman (1953), Verhave (1959), and Clark and Hull (1966) had shown that the rate of lever pressing, or the more refined measure of interresponse interval, as used by Wertheim (1965), may be functionally related to the value of R-S. If holding behavior is modulated by the R-S interval, such temporal response patterning could be explained by noting that changes in the rate of response observed under different R-S values are the outcome of the control of holding behavior by the punishment contingency.…”
mentioning
confidence: 99%
“…In one figure he showed that the model provided excellent fits to the data from five individual animals from four different experiments (Clark & Hull, 1966;Hake, 1968;Sidman, 1953;Verhave, 1959). Although these experiments involved different species (rats, dogs, and monkeys) and different procedures, Gibbon demonstrated that simple quantitative functions based on scalar timing applied to results from all of them.…”
Section: Secondary Analysis Of Published Resultsmentioning
confidence: 99%